A Study the Supply Chain Management and Logistics in the Wind Turbine Manufacturing: Improving Supply Chain Management and Logistics in Wind Turbine Manufacturing Using Six Sigma and Kanban Methods (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In this article, we discuss the issue of Supply Chain Management Logistics in the productionof wind turbines, as well as a possible solution based on Six Sigma methods. Among the tasks involved inthis project was a thorough examination of current procedures at a market leader recommendations forenhancement. The Spanish headquarters of Siemens Gamesa Renewable Energies boasts a globalpresence. Methods used in the American market were studied in order to make adjustments. This wasaccomplished by utilizing the DMAIC Process tool, which is composed of the following 5 steps define,measure, analyze, improve, control. After reviewing the data, it was determined that implementing anew Kanban solution for the organization globally would be beneficial in many ways, particularly interms of improving the correlation between orders, suppliers, resource allocation. This Kanban systemwould be ideal for calculating the availability and capacity of each production plant on a weekly basis comparing these figures to the needs of the orders that need to be performed.